Pelatihan Penyusunan Perangkat Pembelajaran Melalui Model Research Based Learning Bagi Guru Sekolah Laboratorium Universitas Pattimura - Jenny Koce Matitaputty; Anatasija Limba; Elsina Sarah Tamaela; Nessy Pattimukay (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
This community service activity aims to increase partners' insight into the knowledge and skills of Pattimura University Laboratory School teachers in developing learning tools with the Research Based Learning (RBL) model. The target that the implementers want to achieve in this activity is to increase the knowledge and skills of teachers as activity partners, and it is hoped that this knowledge and skills can be applied in the learning process, so that the research skills that have been formed since students were at school can be improved. The method used in implementing the activity is training in developing learning tools using the RBL model for teachers at the Unpatti Laboratory School, from elementary to high school levels. To ensure the training runs smoothly and achieves its targets and expected outcomes, it is necessary to develop a step-by-step activity plan, including preparation, implementation, and evaluation. The method used in this training activity will begin with the material provided is the deep learning approach in the independent curriculum, technology in learning and providing material on the Research Based Learning model, the preparation of learning tools using the Research Based Learning model, and simulation of the application of the learning tools that have been prepared. During the preparation of learning tools and peer teaching, the community service implementation team was directly assisted. The results of community service activities through training activities on preparing learning tools using the RBL model showed that overall the training participants were able to prepare learning tools in the form of RPP and LKPD with a good category, while Technology and teaching materials were in the very good category.